ENGLISH LANGUAGE LEARNING METHOD IN PRESCHOOL EDUCATION - Shamsuddinova Diyoraxon Yorqinbek qizi; Qurbonova Namuna Umidjon qizi (TADQIQOTLAR, 2025)
Annotation: This article examines the most effective methods for teaching English to preschool children. It highlights how early language exposure fosters long- term proficiency and discusses pedagogical strategies including play-based learning, Total Physical Response (TPR), storytelling, and the use of songs and rhymes. The article also emphasizes the importance of a rich, immersive environment and age- appropriate materials to encourage natural language acquisition among young learners.